MAKNA-MAKNA HARF JAR DALAM TERJEMAHAN KITAB BIDÂYATUL HIDÂYAH KARYA ABU ALI AL-BANJARI AN-NADWI Al-MALIKI (April & October, 2025)
This article discusses the meanings of harf jar in the translation of the book harf jar in the translation of the book bidâyatul hidâyah by Abu Ali Al-Banjari An-Nadwi Al-Maliki. This study uses a qualitative method with a descriptive approach to the book Bidâyatul Hidâyah as the object of research. The data used in this study comes from primary data sources, namely the book Bidâyatul Hidâyah, as well as secondary data sources, including various books, articles, journals, and several other relevant scientific works. This researcher focuses on one aspect of nahwu, namely harf jar. Harf jar is a particle that cannot function independently unless it is combined with other words to form meaning. This study produced 46 data containing harf jar in the translation of the book Bidâyatul Hidâyah. From this data, there are several types of relevant harf jar meanings, namely harf jar min (مِنْ), harf jar bi (بِ), harf jar ‘ilâ (إِلَى), harf jar fî (فِيْ), and harf jar ‘alâ (عَلَى). The researcher found 46 data points with different meanings of the prepositions, including the preposition min (مِنْ) in 12 data points, the preposition bi (بِ) in 26 data points, the preposition ‘ilâ (إِلَى) in 3 data points, the preposition fî (فِيْ) with 3 data points, and the preposition ‘alâ (عَلَى) with 2 data points.